Nilai-Nilai Keluarga Sakinah Dalam Tradisi Begalan Banyumasan - Addin’s, Mukhamad â€˜Abdul Khamid (IAIN PONOROGO, 2023)
This research is based on the belief of the Banyumasan people in the tradition in their marriage customs. In the marriage ceremony of this community is known the tradition of the first grandson or daughter-in-law. It is intended as a refusal for both brides in the future family life and as a counsel for both. The ball is played by Joko Sengkolo and Joko Kelheng, both of whom play the ball in a dialogue of humor, with the instrument of the ball as a medium of transformation of the symbolic values contained in it. From the sociological side of its meaning, this tradition has fulfilled the nine functions of the family: religious, biological, caring, education, economics, protection, socialization, recreation, and family status. If both brides can follow this long tradition, the family functions will go well and the family will be peaceful, happy, and prosperous. The focus of this research consists of two issues: 1) the process of implementation of the traditions of begal in the Bathroom marriage and its symbols; and 2) the analysis of the values of the family begal contained in the bathroom marital tradition.